PENGEMBANGAN USAHA BERBASIS POTENSI LOKAL: KAJIAN PADA UKM KALIGRAFI DI KABUPATEN KLATEN DAN KABUPATEN SUKOHARJO JAWA TENGAH - Dewi Ratna Nurhayati, Aris Eddy Sarwono, Ratna Endah Santoso, Narimo & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2016)
Sukoharjo and Klaten district is an area that has a lot of potential, one thatresults craft crafts Calligraphy is already penetrated the export market.Dedication activities through a program of science and technology for exportproducts in the first year is done to address the various problems faced bythe SMEs, both with regard to the production process, managerial ormarketing of its products. IbPE devotion Team Activity is expected toincrease the quality and quantity of products produced calligraphy.Keywords: Calligraphy, Productivity, SMEs, Exports